1989
DOI: 10.3109/02713688908996381
|View full text |Cite
|
Sign up to set email alerts
|

A light microscopic and autoradiographic study of non-irradiated and irradiated ocular wounds

Abstract: Focal gamma irradiation was used to limit the intraocular extension of scar tissue which typically occurs after posterior perforating injury to the eye. Standard posterior perforating injuries were created in the right eye of forty-eight rabbits, half of which had the site of perforation focally irradiated using a Cobalt 60 ophthalmic plaque. Non-irradiated wounds healed with profuse formation of highly cellular and vascularised granulation tissue which invaded the vitreous to form contractile vitreo-retinal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(20 citation statements)
references
References 9 publications
0
20
0
Order By: Relevance
“…Radiotherapy affects the evolution of exudative macular degeneration by endothelial toxicity, resulting in narrowing or occlusion of blood vessels [2,9,13]. Endothelial cells are moderately sensitive to irradiation and vessels may reveal manifestations of radiation injury months to years later [1,2,3,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiotherapy affects the evolution of exudative macular degeneration by endothelial toxicity, resulting in narrowing or occlusion of blood vessels [2,9,13]. Endothelial cells are moderately sensitive to irradiation and vessels may reveal manifestations of radiation injury months to years later [1,2,3,23].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of the effect of ionizing radiation on CNV is not known in detail. Radiotherapy affects the evolution of exudative macular degeneration directly by endothelial toxicity, leading to capillary closure [2], and/or indirectly through its attenuating effects on the inflammatory response, mediated by macrophages and other inflammatory cells [2,9,13].…”
Section: Introductionmentioning
confidence: 99%
“…24,25 The rationale for radiotherapy of ARMD with fairly low doses is to suppress the inflammatory and exudative component of ARMD as well as to inhibit further pathologic endothelial cell proliferation. 17,18,26 All of these features were demonstrated in experimental choroidal neovascularization in rabbit eyes. 27 The degenerative process itself and the persistence of the stimuli that upregulate the growth factors are probably not altered by radiotherapy.…”
mentioning
confidence: 96%
“…In vitro and in vivo experiments demonstrated that irradiation inhibits the proliferation of endothelial cells, reduces the neovascular component of healing ocular wounds and may induce vessel obliteration. [17][18][19][20] Low-dose radiation (p25 Gy) has been shown to cause DNA-breaks, decrease cell replication and reduce prostacyclin synthesis and prostacyclin production. [21][22][23] Radiation also increases cell permeability and induces vascular cell apoptosis in vitro.…”
mentioning
confidence: 99%
“…[10][11][12] IR in combination with either anti-VEGF or anti-platelet-derived growth factor (PDGF), or both, results in enhanced endothelial apoptosis and reduced endothelial cell migration compared with either agent alone. 13 Besides, IR is able to reduce the macrophage-mediated retinal inflammation and causes a capillary closure, both reducing a local oedema of the retina.…”
mentioning
confidence: 99%